POPULATION DYNAMICS OF SUBTERRANEAN CRUSTACEA: ECOLOGY, GENETICS AND CONSERVATION - MELEG, Ioana Nicoleta (2013)
The present study focuses on groundwater fauna from the vadose zone of caves from the Apuseni Mountains. The vadose zone, situated between the soil–epikarst layer (disintegrating rock under the soil) and the phreatic zone, is heterogeneous. The vadose zone is characterized by dissolution voids and fracture fissures in which water percolates downwards by a multiphase process before reaching the phreatic zone.